Sovereignty, statehood and state responsibility : essays in honour of James Crawford - Chinkin, C. M.; Baetens, Freya; Crawford, James, 1948- (Cambridge University Press, 2015)
"This collection of essays focusses on the following concepts: sovereignty (the unique, intangible and yet essential characteristic of States), statehood (what it means to be a State, and the process of acquiring or losing statehood) and State responsibility (the legal component of what being a State entails). The unifying theme is that they have always been and will in the future continue to form a crucial part of the foundations of public international law. While many publications focus on new actors in international law such as international organisations, individuals, companies, NGOs and even humanity as a whole, this book offers a timely, thought-provoking and innovative reappraisal of the core actors on the international stage: States. It includes reflections on the interactions between States and non-state actors and on how increasing participation by and recognition of the latter within international law has impacted upon the role and attributes of statehood"--